The Economics of Career Concerns, Part I: Comparing Information Structures - Dewatripont, Mathias; Jewitt, Ian; Tirole, Jean (Review of Economic Studies, 1999)
Many incentives in organizations arise not through explicit formal incentive contracts but rather implicitly through career concerns. This paper models career concerns through agents trying to manipulate the market assessment of their future productivity. The information flow from current actions to market assessment is therefore crucial in determining the nature of these incentives. Improved information may either increase or reduce incentives. The impact of information provides a major distinction between the explicit and implicit incentives model. The paper derives general results on comparisons of information structures which serve as counterparts to the standard results on information structures in the principal-agent model: sufficient statistic, impact of a Blackwell garbling, comparison of inclusive information structures.